Development of batik scarf design based on the architecture of the great mosque of Gresik as a representation of local cultural identity - Deny Arifiana; Inty Nahari; Shofi Aliya Putri; Indarti Indarti (Gelar: Jurnal Seni Budaya, 2026)
Contemporary batik design research has extensively addressed the preservation of traditional motifs, the transformation of regional icons, and the utilization of digital technologies. However, studies that specifically translate the religious architectural elements of the Great Mosque of Gresik into batik scarf designs remain limited, particularly those that integrate reflections on creative practice, structured evaluation, and prototype realization. This study aims to develop the Agung Prasaja batik scarf design based on the architecture of the Great Mosque of Gresik and to elucidate its contribution to culture based textile design. The method employed is Practice led Research, supported by descriptive quantitative evaluation. The research stages include visual context exploration, architectural element mapping, motif stylization, digital composition development at 160 × 35 cm, design evaluation, and the realization of three selected batik tulis (hand-drawn batik) scarf prototypes. The evaluation instrument utilized a 1–5 scale with 11 indicators grouped into the aspects of aesthetics, symbolic cultural legibility, application potential, and user appeal. The evaluation involved 30 informed design assessors/users. The findings produced eight primary motif units and ten design alternatives. The three designs prioritized for batik tulis scarf prototype realization were Agung Prasaja 5, Agung Prasaja 4, and Agung Prasaja8. The findings indicate that design strength is determined not solely by the beauty of motifs but also by visual hierarchy, the legibility of architectural symbols, and suitability for the scarf format. The contribution of this research lies in offering a measurable, reflective, and applicable model for transforming local religious architecture into contemporary textile design, thereby supporting the development of Gresik batik products.